SERAPAN NITROGEN, FOSFOR DAN KALIUM BOKASHI TINJA OLEH TANAMAN JAGUNG - Widowati Widowati; Sutoyo Sutoyo (Universitas Tribhuwana Tunggadewi, 2007)
A glasshouse experiment was conducted to elucidate the effect of feces bokhasi (FB) on uptake of N, P and K by maize grown on an Inceptisol. Nine treatments comprising eight FB rates of 2,5, 5, 7,5, 12,5, 15, 17,5 and, 20 t FB/ha and one control (no added FB) were arranged in a completely randomized design with three replicates. Results of the experiment showed that application of FB up to 10 t/ha increased plant NPK contents. However, applications of more than 10 FB/ha reduced N and K uptake by maize, while P uptake was kept steady. The highest uptake of N, P and K was observed for application of 10 t/ha. i.e. 121.86 , 13.21, and 68.27 mg/kg respectively. Application of various rates of FB did not significantly (P = 5%) affect uptake of N, P and K by plant, but significantly affected K uptake. The average N loss from all treatments ranged from 14.4 to 15,5 mg/kg; the average loss of P from all treatment was about 2,2 mg/kg, and the average loss of K from all treatments ranged from 2,1 to 2,2 mg/kg. The lowest NPK recovery was observed for 20 t FB/ha treatment, i.e. 0,64%, 4,51%, and 18,18%, respectively, whereas the highest NPK recovery was observed for 10 t FB/ha treatment, i.e. 20,43%, 27,16%, and 67,90%, respectively